No evidence for Ago2 translocation from the host erythrocyte into the Plasmodium parasite - Hentzschel, Franziska (Wellcome Open Res, 2020)
Background: Plasmodium parasites rely on various host factors to grow and replicate within red blood cells (RBC). While many host proteins are known that mediate parasite adhesion and invasion, few examples of host enzymes co-opted by the parasite during intracellular development have been described. Recent studies suggested that the host protein Argonaute 2 (Ago2), which is involved in RNA interference, can translocate into the parasite and affect its development. Here, we investigated this hypothesis. Methods: We used several different monoclonal antibodies to test for Ago2 localisation in the human malaria parasite, P. falciparum and rodent P. berghei parasites. In addition, we biochemically fractionated infected red blood cells to localize Ago2. We also quantified parasite growth and sexual commitment in the presence of the Ago2 inhibitor BCI-137. Results: Ago2 localization by fluorescence microscopy produced inconclusive results across the three different antibodies, suggesting cross-reactivity with parasite targets. Biochemical separation of parasite and RBC cytoplasm detected Ago2 only in the RBC cytoplasm and not in the parasite. Inhibition of Ago2 using BCl-137 did not result in altered parasite development. Conclusion: Ago2 localization in infected RBCs by microscopy is confounded by non-specific binding of antibodies. Complementary results using biochemical fractionation and Ago2 detection by western blot did not detect the protein in the parasite cytosol, and growth assays using a specific inhibitor demonstrated that its catalytical activity is not required for parasite development. We therefore conclude that previous data localising Ago2 to parasite ring stages are due to antibody cross reactivity, and that Ago2 is not required for intracellular Plasmodium development.